Effect of Bi2O3 content on optical and radiation shielding properties of (Na2O, K2O)-SiO2-CaO-Al2O3-B2O3 glass system - Dararutana P. (2014)
Glasses of (Na2O, K2O)-SiO2-CaO-Al2O3-B2O3 system with 5-40 wt% in concentration variations of Bi2O3 were fabricated in a laboratory scale using the conventional melting technique. Both refractive indices and densities of the glass samples were measured using a refractometer and the Archimedean buoyancy method, respectively, at 25°C. The gamma attenuation characteristics of the samples were studied using the photon energy of 662 keV from Cs-137. It was found that the values of refractive index and density of the samples increased and that their colors turned from colorless to yellow with increasing Bi2O3 contents. The relationship between refractive indices, densities, attenuation coefficients and Bi2O3 introducing contents were plotted and discussed. The results suggested that bismuth-bearing glass can be used as an environmental-friendly substitute for lead- and/or barium-bearing glasses for industries besides their radiation-shielding property.